Praxial visions for classical music education in the 21st century - Rusu, Irina (Taideyliopiston Sibelius-Akatemia, 2017)
Even though the overall level of education has improved significantly in the past years, there are still quite many cases of teachers who don't acknowledge the real meaning of their profession. The aim of this research is to explore how teachers, in different sociocultural contexts, understand the purpose of their work in contemporary music education. Outlining from semi-structured interviews of three novice teachers the author is defining what a good teachers' vision is and cultivating a sense of purpose. Drawing upon praxial approaches to music education, to understand teaching as demanding source of something is more than just being a specialist in a particular music field, or a virtuosic performer. Placing music as a central abstraction to which refers listening, performing, educating, learning, composing, improvising and many others - all are and will be ethically, socially, politically, emotionally, philosophically idealized. The theoretical frame for this research draws upon the works of Elliott and Silverman (2015) and Karen Hammerness (2006). The concept of social praxis about education, teaching and learning, cultivating and facilitating claims that all institutional subjects, experiences and aims has to pledge students' life values and goals. Without foundational theories and principles about what we do and how we should act as teachers and musicians, we won't be involved in praxis.
Keywords: oppiminen; visiot; teoriat; musiikkikasvatus; fi=musiikkikasvatus|sv=musikpedagogik|en=Music Education|